NILAI BUDAYA DALAM SYAIR ROKAN HILIR KARANGAN AHMAD DARMAWI - Yeni Maulina (Balai Bahasa Provinsi Riau, 2015)
This study closely motivated by the existence and the diversity of cultural values found in literary works. One of the old literary works that has cultural value is poetry (syair). Syair Rokan Hilir written by Ahmad Namawi obtained a descriptive overview of the cultural values include values of faith, gratitude, respecting each other, helping each other, keeping honors, leadership, deliberation, fairness, and politeness.